Mobile Learning in Malaysian Universities: Are Students Ready? - Ismail, Issham; Azizan, Siti Norbaya; Gunasegaran, Thenmolli (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Prior to embarking on mobile learning, it is critical for learning institutions to research the area of finding the right ingredient for the right learners by firstly seeking whether they are ready to adapt to the mobility of learning. Adding a Malaysian perspective, the purpose of this paper was to present a quantitative study on university students’ readiness for the integration of mobile technologies in education system within their learning institutions. The study was carried out in 11 public universities in Malaysia, whereby 55 questionnaires were randomly distributed to students in each campus. Out of a total of 605 questionnaires distributed, 551 were returned. Overall, the descriptive results were relatively neutral and thus, indicating that they were moderately ready for the educational use of mobile technology. Furthermore, some were quite concerned on cost issue. Despite this, respondents were somewhat agree that they are interested to know more about mobile learning. As a result of the data analysis, some important issues emerged which give rise to the importance of assessing students’ readiness for a successful implementation of mobile learning. These findings may function as anchor-points for further research should mobile learning is to be employed widely in Malaysian higher education setting.